Virtual antenatal clinics. (2nd September 2020) - Quinn, Lauren; Olajide, Oluwafumbi; Breslin, Eamonn; Tan, Bee; Ansar, Humera
Abstract : In the current COVID-19 pandemic, a move towards virtual appointments has been vital. This article discusses the implementation of virtual antenatal clinics and the associated challenges